Seleção de basidiomicetos da região Amazônica com potencial para degradação de benzo(a)pireno - Santos, Vanderlei Saboia dos (2017)
Basidiomycetes fungi are well known for their macroscopic forms, such as mushrooms and wood ear, and play an important role in the cycling of nutrients in ecosystems. Currently, studies report the importance of basidiomycetes in degrading environmental contaminants through the use set of low specificity ligninolytic enzymes. The objective of this work is to select basidiomycetes isolated from the Amazon region that present potential for Benzo(a)Pyrene (BaP) degradation. The isolates were pre-selected for the ability in oxidize gallic acid to quinone, this assay indicates the presence of ligninolytic enzymes important for degradation of xenobiotics, in sequence, the isolates were evaluated for potential to discolor the Remazol Brilliant Blue R (RBBR) dye derived from Anthracene. The selected fungi were used in assays to evaluate the activity of lignolytic enzymes (Lacase, Lignin Peroxidases and Manganese Peroxidase) in the presence of RBBR dye and BaP. Fungi that showed enzymatic activity in the presence of xenobiotics were selected for in vitro biodegradation assays of BaP, BaP metabolism analysis was also performed. Of the fungal isolates, 42% presented results for gallic acid oxidation with highlight for two fungal isolates (UEAF26-2 and UEAF06-2). The isolate UEAF26-2 showed production of MnP (12.73 IU L-1) and LiP (21.65 IU L-1) with highlight Lacase (78.4 IU L-1) in enzymatic activity assay with RBBR obtained 94% discoloration in 24 hours for the concentration of 100 mgL-1 of RBBR. In enzymatic activity assays using BaP as inducer the isolate presented LiP production (1.15 IU L-1), with emphasis on Lacase (28, 52 IU L-1). The isolate UEAF06-2 showed production for Lacase (22.17 IU L- 1), MnP (9.91 IU L-1) and LiP (8.89 IU L-1) and in 24 hours discolored 38% of the dye to 100 mgL-1 concentration of RBBR. In assays using BaP as an inducer of enzyme activity, the isolate obtained results for Lacase (4.46 IU L-1) and LiP (1.59 IU L-1). In a BaP degradation assay (1mg L-1), the isolate UEAF26-2 showed 9.9% in 7 days and 7.4% in 14 days. Isolate UEAF06-2 presented degradation of 13% in 7 days and 42.3% for 14 days with BaP (1mg L- 1). In analysis of BaP metabolites, the analyzed metabolites (coumarin and 1-hydroxysilane-2- naphthoic acid) were not detected. The results highlight the potential of isolate UEAF06-2 for degradation of BaP and the use of this fungus in later tests of degradation of other HPAs. Keywords: Basidiomycetes from Amazon, Ligninolytic enzymes, biodegradation, Benzo(a)Pyrene.